Reducing anxiety and attentional bias with reward association learning and attentional bias modification - Xiao, Wen; Zheng, Xiaoqi; Luo, Yuejia; Peng, Jiaxin (Frontiers in Psychology, 2022)
The current study examined the effects of a reward associative learning procedure and the traditional threat-avoidance ABM paradigm on anxiety and attentional bias. In reward training, participants were given high rewards for correct responses to neutral target and low rewards for correct responses to negative target. In reward control training, participants received no cues of rewards after their responses. High trait anxious individuals (N = 76) first completed a session of reward training or reward control training, followed by four sessions of ABM training or ABM control training. Generalized anxiety disorder symptom (GAD-7) and attentional bias in a dot-probe task were assessed during pre- and post-training. Results indicated that the effect of ABM training on reducing anxiety was only obtained in the reward training condition. Participants who received reward training showed significantly less attentional bias compared with those receiving reward control training. There was no significant training effect of ABM on atttentiona bias. Results suggested that reward training reduced general anxiety and attentional bias. Traditional ABM training reduced anxiety only when combined with reward training. Attentional bias in anxiety are modifiable through reward training.